Coverage and aggregation of gold nanoparticles on silanized glasses - Scarpettini, Alberto Franco (2010)
We study the dynamics of the coverage and aggregation of gold nanoparticles over organosilanized glass substrates for different sizes of nanoparticles. We present measurements of extinction spectra and nanoparticle counting statistics and demonstrate that both methods are equivalent describing those processes. We introduce models that describe the mentioned dynamics, which are characterized by an exponential-like function with two relevant parameters: a saturation value and a characteristic time. The electrostatic repulsion plays a significant role in both processes. The aggregation is dominated by the mobility of the isolated nanoparticles, which first join in dimers and, further in time, in clusters of higher number of nanoparticles. © 2010 American Chemical Society.